Introduction "Mangrove" Ecoliteracy for IPS Learning on Elementary School - Herawati, Ignasia Anggi; Supriatna, Nana; Sulastri, Sulastri (International Conference on Elementary Education, 2020)
Mangroves are now increasingly rare in Indonesian waters because almost all of the mangroves have been damaged. This is certainly very alarming considering that mangroves actually have a very important role for the survival of all living things. Referring to the problem, it is necessary to introduce ecoliteracy of "mangroves" as a small action aimed at inviting students to save mangrove ecosystems that have been damaged one of the ways by replanting mangrove plants around the waters, to instill students' caring attitudes towards the environment and foster a student's love for environment. The method used in this research is literature study which refers to literature review in the form of articles in journals, books, and other reliable sources related to the research title. Based on the results of the study, explaining that in social studies learning at school students not only acquire basic theories but also the need to develop social skills possessed by students specifically in maintaining and preserving mangroves